President's Message: Carpe Diem! "Seize the Day" - Farid, Donna (Operating Room Nurses Association of Canada Journal, 1998)
The message could not have been made more clear at the 1998 CNA Biennium and National Nursing Forum in Ottawa last June. The theme of the National Nursing Forum "From Voice to Action: A Nursing Agenda for a Healthier Canada" was firmly reinforced by the two speakers who set the tone for the day. Joan Marie Aylward, Health Minister from Newfoundland, and who, by the way, still maintains her RN License, urged nurses to work together in delivering a clear message promoting the value of our work, and protecting our publicly funded health care system. Dr. Patricia McKeever, from the University of Toronto, addressed the issue of the burden of home care falling on the shoulders of unpaid family members - mostly women - who are "footing the bill for the bricks and mortar of our health care system", making for additional inequities. Participants divided into smaller groups, reviewed the strategies developed at the ﬁrst Forum, identiﬁed further projects and concluded by discussing what was the most important message for nurses to be sending within the next six months.